Effects of Unemployment on Crime in selected Sub-Sahara African countries - Sézard, Timbi; Eric, Ayang; Missa Daniel, Toumpiguim (International Journal of Scientific Research and Management (IJSRM), 2021)
The objective of this study is to assess the effect of unemployment on crime in Sub-Saharan Africa. The main contribution of this study is in the enrichment of the literature on this phenomenon which is common throughout the African continent. The study covers 40 SSA countries and is based on the two-stage Generalized Method of Moments (GMM) inspired by the empirical model of Raphael and Winter-Ebmer (2001) between 1990 and 2018. Youth unemployment rate is found to have a positive and significant effect on the rate of murder in SSA countries.